Laminate for packaging material and packaging material
The laminate for packaging materials, featuring a substrate and heat sealing layer made of the same polyolefin resin, addresses the recyclability challenge of conventional packaging by enhancing strength, heat resistance, and recyclability while maintaining barrier and printing properties.
Patent Information
- Application Number
- JP2025008077
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-10
AI Technical Summary
Conventional packaging materials are difficult to recycle due to the use of different resin materials for the substrate and heat sealing layer, which hinders recyclability and sustainability.
A laminate for packaging materials comprising a substrate, a gas barrier laminate, and a heat sealing layer, where the substrate and heat sealing layer are made of the same polyolefin resin, and the gas barrier laminate includes a gas barrier resin layer and a polyolefin resin layer, with a high polyolefin content to enhance recyclability.
The solution achieves high strength, heat resistance, and recyclability of packaging materials while maintaining excellent barrier properties and printing suitability.
Smart Images

Figure 2025061505000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate for packaging materials and a packaging material comprising said laminate. [Background technology]
[0002] Conventionally, resin films made of resin materials have been used as a constituent material of packaging materials. For example, resin films made of polyolefins have appropriate flexibility and transparency as well as excellent heat sealability, and therefore are widely used as packaging materials.
[0003] Normally, resin films made of polyolefins cannot be used as substrates because they are inferior in strength and heat resistance, and are therefore laminated with resin films made of polyester, polyamide, etc. For this reason, typical packaging materials are made of laminated films in which the substrate and heat seal layer are made of different materials (for example, Patent Document 1).
[0004] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a demand for packaging materials with high recyclability. However, conventional packaging bodies are composed of different resin materials as described above, and since it is difficult to separate each resin material, they are not currently recycled. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-202519 A Summary of the Invention [Problem to be solved by the invention]
[0006] The inventors have discovered that by forming a polyolefin resin, which has conventionally been used as a heat seal layer, into a stretched resin film and using the substrate as a base material, and laminating the substrate with a heat seal layer composed of polyolefin, it is possible to obtain a recyclable packaging material while maintaining the strength and heat resistance required for the packaging material. In addition, the inventors have found that by providing a gas barrier laminate, which is a stretched resin film, between the substrate and the heat seal layer, it is possible to improve strength and barrier performance while maintaining recyclability.
[0007] The present invention has been made in view of the above findings, and an object of the present invention is to provide a laminate for packaging materials that can realize a packaging material that has excellent recyclability while also having the strength and barrier properties required for a packaging material. Another object of the present invention is to provide a packaging material comprising the laminate for packaging materials. [Means for solving the problem]
[0008] The laminate for packaging material of the present invention includes at least a substrate, a gas barrier laminate, and a heat seal layer, the substrate and the gas barrier laminate are stretched resin films, The gas barrier laminate comprises a gas barrier resin layer and a polyolefin resin layer, The substrate, the polyolefin resin layer and the heat seal layer are made of the same polyolefin, The thickness of the gas barrier resin layer is smaller than the thickness of the polyolefin resin layer.
[0009] In one embodiment, the content of the polyolefin in the entire laminate for a packaging material is 80 mass % or more.
[0010] In one embodiment, the laminate for packaging materials of the present invention has a deposition layer at least one between the substrate and the gas barrier laminate and between the gas barrier laminate and the heat seal layer.
[0011] In one embodiment, the laminate for a packaging material of the present invention has an adhesive layer between the substrate and the vapor-deposited film, and between the gas barrier laminate and the vapor-deposited film.
[0012] In one embodiment, the vapor-deposited film is an aluminum vapor-deposited film. The adhesive layer contains a cured product of a resin composition that contains a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound.
[0013] In one embodiment, the gas barrier laminate includes an adhesive resin layer between the gas barrier resin layer and the polyolefin resin layer.
[0014] The packaging material of the present invention is characterized in that it is composed of the above-mentioned laminate. Effect of the Invention
[0015] According to the present invention, it is possible to provide a laminate for packaging materials having high recyclability.
[0016] Furthermore, according to the present invention, it is possible to provide a laminate for packaging materials having high strength, heat resistance, printability, oxygen barrier properties and water vapor barrier properties.
[0017] Furthermore, according to the present invention, a packaging material constituted by the laminate for packaging materials can be provided. [Brief description of the drawings]
[0018] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Figure 4] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Diagram 5] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Figure 6] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Figure 7] 1 is a schematic cross-sectional view showing one embodiment of a laminate for packaging material of the present invention. [Figure 8] FIG. 1 is a perspective view showing one embodiment of a packaging material produced using the laminate for packaging materials of the present invention. [Figure 9] FIG. 1 is a perspective view showing one embodiment of a packaging material produced using the laminate for packaging materials of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] (Laminate for packaging materials) As shown in FIG. 1, the laminate 10 for a packaging material of the present invention comprises at least a substrate 11, a gas barrier laminate 12, and a heat seal layer 13, and the gas barrier laminate 13 comprises a gas barrier resin layer 14 and a polyolefin resin layer 15.
[0020] In one embodiment of the present invention, the laminate 10 for a packaging material may have a vapor deposition layer 16 at least either between the substrate 11 and the gas barrier laminate 12 or between the gas barrier laminate 12 and the heat seal layer 13, as shown in Figs. 2 and 3.
[0021] In one embodiment of the present invention, the laminate 10 for a packaging material may further include an adhesive layer 17 between the substrate 11 and the vapor-deposited film 16 as shown in FIG. 4, or between the gas barrier laminate 12 and the vapor-deposited film 16 as shown in FIG. 5.
[0022] In one embodiment of the present invention, the packaging material laminate 10 may further include an adhesive resin layer 18 between the gas barrier resin layer 14 and the polyolefin resin layer 15, as shown in FIG.
[0023] In one embodiment of the present invention, the heat seal layer 13 of the laminate for packaging materials 10 may include a first heat seal layer 19 and a second heat seal layer 20, as shown in FIG.
[0024] Furthermore, in one embodiment of the present invention, the laminate for packaging material 10 may have a gas barrier coating film between any of the layers (not shown).
[0025] The polyolefin content in the entire laminate for packaging materials of the present invention is preferably 80% by mass or more, and more preferably 90% by mass or more. By making the polyolefin content in the entire laminate for packaging material of the present invention 80% by mass or more, the recyclability of the laminate for packaging material of the present invention can be improved. The polyolefin content in the laminate for packaging materials means the ratio of the polyolefin content to the sum of the contents of the resin materials in each layer constituting the laminate.
[0026] Each layer constituting the laminate for packaging material of the present invention will be described below.
[0027] (base material) The substrate provided in the laminate for packaging material of the present invention is composed of a polyolefin, and this polyolefin is the same as the polyolefin constituting the polyolefin resin layer and the heat seal layer described below. By using the same resin for the substrate, the same resin for the polyolefin resin layer, and the same resin for the heat seal layer, the recyclability of the laminate for packaging materials can be improved.
[0028] In order to maintain the strength and heat resistance required for a packaging material, a stretched resin film made of polyolefin is used as the substrate. The stretched resin film may be either a uniaxially stretched resin film or a biaxially stretched resin film.
[0029] The stretching ratio in the machine direction (MD) of the stretched resin film is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By making the stretching ratio of the stretched resin film in the machine direction (MD) 2 times or more, the strength and heat resistance of the laminate for packaging material of the present invention can be improved. In addition, since the transparency of the substrate can be improved, when an image is formed on the adhesive layer side surface of the substrate, the visibility of the image can be improved. On the other hand, the upper limit of the stretching ratio in the machine direction (MD) of the stretched resin film is not particularly limited, but it is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.
[0030] The stretching ratio in the transverse direction (TD) of the stretched resin film is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By making the stretching ratio of the stretched resin film in the transverse direction (TD) 2 times or more, the strength and heat resistance of the laminate for packaging material of the present invention can be improved. In addition, since the transparency of the substrate can be improved, when an image is formed on the adhesive layer side surface of the substrate, the visibility of the image can be improved. On the other hand, the upper limit of the stretching ratio in the transverse direction (TD) of the stretched resin film is not particularly limited, but it is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.
[0031] The polyolefin that can be used as the substrate must be the same as the polyolefin that constitutes the polyolefin resin layer and the heat seal layer as described above. Examples of such polyolefins include polyethylene, polypropylene, polymethylpentene, ethylene-propylene copolymers, and propylene-butene copolymers. Among these, polyethylene and polypropylene are preferred.
[0032] As polyethylene, it has a density of 0.945 g / cm 3 Ultra-high density polyethylene (HDPE), density 0.925~0.945g / cm 3 Medium density polyethylene (MDPE), with a density of 0.925 g / cm3 Examples of low density polyethylene include low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
[0033] In one embodiment, the substrate may have a structure including a layer containing high density polyethylene and a layer containing medium density polyethylene. By providing a high-density polyethylene layer on the outer side of the substrate, the strength and heat resistance of the laminate for packaging materials of the present invention can be improved, and by providing a medium-density polyethylene layer, the stretchability of the resin film constituting the substrate can be improved.
[0034] For example, it has a structure consisting of a high density polyethylene layer / medium density polyethylene layer from the outside. By adopting such a constitution, it is possible to improve the stretchability of the film, and also to improve the strength and heat resistance of the laminate for packaging material of the present invention. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate for packaging materials of the present invention can be improved. Also, by setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 1 or less, the stretchability of the film can be improved.
[0035] Also, for example, it may be configured from the outside in a high density polyethylene layer / medium density polyethylene layer / high density polyethylene layer. By adopting such a constitution, it is possible to improve the stretchability of the film, to improve the strength and heat resistance of the laminate for packaging material of the present invention, and to prevent the occurrence of curling in the substrate. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate for packaging materials of the present invention can be improved. Also, by setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 1 or less, the stretchability of the film can be improved.
[0036] Also, for example, the laminate may be configured from the outside in a high-density polyethylene layer / medium-density polyethylene layer / low-density polyethylene layer or a linear low-density polyethylene layer / medium-density polyethylene layer / high-density polyethylene layer. By adopting such a constitution, the stretchability of the film can be improved. In addition, the strength and heat resistance of the laminate for packaging material of the present invention can be improved. In addition, the occurrence of curling in the substrate can be prevented. Furthermore, the processability of the film can be improved. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate for packaging materials of the present invention can be improved. Also, by setting the ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer to be 1 / 1 or less, the stretchability of the film can be improved. In addition, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the low density polyethylene layer or the linear low density polyethylene layer. The ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or the linear low-density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By making the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or the linear low-density polyethylene layer 1 / 10 or more, the heat resistance can be improved. Furthermore, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer or the linear low-density polyethylene layer to 1 / 1 or less, the processability in stretching can be improved.
[0037] The polypropylene may be a homopolymer, a random copolymer or a block copolymer. A polypropylene homopolymer is a polymer of propylene alone, a polypropylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene (e.g., ethylene, butene-1, 4-methyl-1-pentene, etc.), and a polypropylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of the above-mentioned α-olefin other than propylene. Among these polypropylenes, it is preferable to use a homopolymer or a random copolymer from the viewpoint of improving the transparency of the substrate and improving the visibility of an image formed on the adhesive layer side surface of the substrate. When the rigidity and heat resistance of the packaging material are important, a homopolymer can be used, and when impact resistance and the like are important, a random copolymer can be used.
[0038] In addition, as a raw material for obtaining polyolefin, an olefin monomer derived from biomass may be used instead of an olefin monomer derived from fossil fuel. Since such an olefin monomer derived from biomass is a carbon-neutral material, it can be used as a packaging material with even less environmental impact. Such biomass-derived polyolefins, such as polyethylene, can be produced by the method described in JP 2013-177531 A. Commercially available biomass-derived polyolefins (e.g., Green PE available from Braskem) may also be used.
[0039] Polyolefins recycled by mechanical recycling can also be used. Mechanical recycling generally refers to a method in which recovered polyolefin films are crushed and washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse and decontaminate the contaminants remaining inside the film, removing the dirt from the polyolefin film and returning it to polyolefin.
[0040] The substrate may have an image formed on its surface. The image may be formed on either side of the substrate, but it is preferable to form the image on the adhesive layer side, since this can prevent contact with the outside air and deterioration over time. The image to be formed is not particularly limited, and may be a character, a pattern, a symbol, or a combination thereof. The image can be formed using a conventionally known ink, but is preferably formed using an ink derived from biomass, which allows the laminate of the present invention to be used to produce a packaging material with less environmental impact. The method for forming the image is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, flexographic printing, etc. Among these, flexographic printing is preferred because it can reduce the environmental load.
[0041] In addition, the substrate is preferably subjected to a surface treatment, which can improve adhesion to adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals. Furthermore, an anchor coat layer may be formed on the surface of the substrate using a conventionally known anchor coat agent.
[0042] The thickness of the substrate is preferably 5 μm or more and 300 μm or less, and more preferably 7 μm or more and 100 μm or less. By making the thickness of the substrate 5 μm or more, the strength of the laminate for packaging material of the present invention can be improved, and by making the thickness of the substrate 300 μm or less, the processability of the laminate for packaging material of the present invention can be improved.
[0043] The substrate can be prepared by forming a polyolefin into a film by a T-die method, an inflation method or the like, and then stretching the film. According to the inflation method, film formation and stretching can be carried out simultaneously.
[0044] When the substrate is produced by the T-die method, the MFR of the polyolefin is preferably 5 g / 10 min or more and 20 g / 10 min or less. By setting the MFR of the polyolefin to 5 g / 10 min or more, the processability of the laminate for packaging materials of the present invention can be improved, and by setting the MFR of the polyolefin to 20 g / 10 min or less, the resin film can be prevented from breaking.
[0045] When the substrate is produced by an inflation method, the MFR of the polyolefin is preferably 0.5 g / 10 min or more and 5 g / 10 min or less. By making the MFR of the polyolefin 0.5 g / 10 min or more, the processability of the laminate for packaging materials of the present invention can be improved, while by making the MFR of the polyolefin 5 g / 10 min or less, the film formability can be improved.
[0046] The substrate is not limited to those prepared by the above method, and commercially available substrates may be used.
[0047] (Gas barrier laminate) The laminate for packaging material of the present invention comprises a gas barrier laminate including at least a gas barrier resin layer and a polyolefin resin layer. By providing the packaging material laminate of the present invention with such a gas barrier laminate, it is possible to improve its strength, oxygen barrier property and water vapor barrier property.
[0048] In one embodiment, the gas barrier laminate may further include an adhesive resin layer between the gas barrier resin layer and the polyolefin resin layer. By further providing an adhesive resin layer between the gas barrier resin layer and the polyolefin resin layer, the adhesion between these layers can be further improved.
[0049] In the present invention, the thickness of the gas barrier resin layer is smaller than the thickness of the polyolefin resin layer. By adopting such a configuration, the recyclability of the packaging material laminate of the present invention can be improved. The thickness of the gas barrier resin layer is preferably 5 μm or more smaller than the thickness of the polyolefin resin layer, and more preferably 10 μm or more smaller. By making the thickness of the gas barrier resin layer 5 μm or more smaller than the thickness of the polyolefin resin layer, the recyclability of the packaging material laminate of the present invention can be further improved.
[0050] The gas barrier laminate is composed of a stretched resin film, and the stretched resin film may be either a uniaxially stretched resin film or a biaxially stretched resin film.
[0051] The stretching ratio in the machine direction (MD) of the stretched resin film is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By setting the stretching ratio in the longitudinal direction (MD) of the stretched resin film to 2 times or more, the strength of the laminate for packaging material of the present invention can be improved while maintaining the oxygen barrier property and water vapor barrier property. On the other hand, the upper limit of the stretching ratio in the longitudinal direction (MD) of the stretched resin film is not particularly limited, but is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.
[0052] The stretching ratio in the transverse direction (TD) of the stretched resin film is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By setting the stretching ratio in the transverse direction (TD) of the stretched resin film to 2 times or more, the strength of the laminate for packaging material of the present invention can be improved while maintaining the oxygen barrier property and water vapor barrier property. On the other hand, the upper limit of the stretching ratio in the transverse direction (TD) of the stretched resin film is not particularly limited, but is preferably 10 times or less from the viewpoint of the breaking limit of the stretched film.
[0053] (Gas barrier resin layer) The gas barrier resin layer constituting the heat seal layer contains at least one type of gas barrier resin, for example, ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic resins, and among these, EVOH is preferred from the viewpoints of oxygen barrier properties and water vapor barrier properties.
[0054] The ethylene content in EVOH is preferably from 20% by mass to 60% by mass, and more preferably from 27% by mass to 48% by mass. By adjusting the ethylene content in the EVOH to 20% by mass or more, the processability of the laminate for packaging materials of the present invention can be improved, and by adjusting the ethylene content in the EVOH to 60% by mass or less, the oxygen barrier property and water vapor barrier property of the laminate for packaging materials of the present invention can be improved.
[0055] The content of the gas barrier resin in the gas barrier resin layer is preferably 50% by mass or more, and more preferably 75% by mass or more. By adjusting the content of the gas barrier resin in the gas barrier resin layer to 50% by mass or more, the oxygen barrier property and water vapor barrier property of the packaging material laminate of the present invention can be further improved.
[0056] The content of the gas barrier resin in the entire laminate for packaging material of the present invention is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting the content of the gas barrier resin in the entire laminate for packaging materials to 20% by mass or less, the recyclability of the laminate for packaging materials of the present invention can be improved.
[0057] The gas barrier resin layer may contain additives within the range that does not impair the characteristics of the present invention, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, compatibilizers, and pigments.
[0058] The thickness of the gas barrier resin layer is preferably 0.5 μm or more and 10 μm or less, and more preferably 1 μm or more and 7 μm or less. By making the thickness of the gas barrier resin layer 0.5 μm or more, the oxygen barrier property and water vapor barrier property of the packaging material laminate of the present invention can be improved, and by making the thickness of the gas barrier resin layer 10 μm or less, the recyclability of the packaging material laminate of the present invention can be improved.
[0059] (Polyolefin resin layer) The polyolefin resin layer is characterized by being composed of the same polyolefin as the polyolefin constituting the above-mentioned substrate and the below-mentioned heat seal layer. By adopting such a composition, it is possible to obtain a recyclable packaging material while maintaining the strength and heat resistance as a packaging material.
[0060] The thickness of the polyolefin resin layer is preferably 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less. By making the thickness of the polyolefin resin layer 5 μm or more, the strength, heat resistance and recyclability of the packaging laminate of the present invention can be improved, while by making the thickness of the polyolefin resin layer 100 μm or less, the processability of the packaging laminate of the present invention can be improved.
[0061] (adhesive resin layer) In one embodiment, the heat seal layer may include an adhesive resin layer between the gas barrier resin layer and the polyolefin resin layer, which can improve the adhesion between the gas barrier resin layer and the polyolefin resin layer.
[0062] The adhesive resin layer contains at least one resin material, for example, polyolefin, modified polyolefin, polyester, vinyl resin, polyamide, etc. Among these, polyolefin and modified polyolefin are preferred from the viewpoints of recyclability and adhesion.
[0063] The adhesive resin layer may contain the above-mentioned additives within the range that does not impair the characteristics of the present invention.
[0064] The thickness of the adhesive resin is preferably 0.5 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. By making the thickness of the adhesive resin layer 0.5 μm or more, the adhesion between the gas barrier resin layer and the polyolefin resin layer can be improved, and by making the thickness of the adhesive resin layer 10 μm or less, the recyclability of the packaging laminate of the present invention can be improved.
[0065] The gas barrier laminate can be produced by co-extrusion of the material constituting the gas barrier resin layer and the material constituting the polyolefin resin layer (and the material constituting the adhesive resin layer, if present) using a conventionally known method such as the T-die method or the inflation method, and stretching the resulting film.
[0066] (Heat seal layer) The heat seal layer is characterized by being composed of the same polyolefin as the polyolefin that composes the above-mentioned substrate and polyolefin resin layer. That is, the resin that can be used for the heat seal layer is the same as the polyolefin used for the above-mentioned substrate and polyolefin resin layer. By adopting such a composition, it is possible to obtain a recyclable packaging material while maintaining the strength and heat resistance as a packaging material. However, the heat seal layer is formed from an unstretched polyolefin resin film or by melt extrusion.
[0067] In addition, when polypropylene is used as the resin constituting the heat seal layer, a heat seal modifier may be included to improve the heat sealability. The heat seal modifier is not particularly limited as long as it has excellent compatibility with the polyolefin constituting the heat seal layer, and examples thereof include olefin copolymers.
[0068] The thickness of the heat seal layer is preferably from 5 μm to 100 μm, and more preferably from 10 μm to 50 μm. By making the thickness of the heat seal layer 5 μm or more, the heat sealability and recyclability of the heat seal layer can be improved, and by making the thickness of the heat seal layer 100 μm or less, the processability of the laminate for packaging material of the present invention can be improved.
[0069] In one embodiment, the heat seal layer may have a multi-layer structure. In particular, when a heat seal modifier is added to polypropylene as the heat seal layer, the modifier may migrate (bleed) to the gas barrier laminate, so the heat seal layer may be made of two or more layers, with the heat-sealed side (the innermost layer side of the laminate) being a layer containing polyolefin and heat seal modifier, and the outer layer being a layer made of polyolefin. That is, the multi-layer structure may include a multi-layer structure consisting of a first heat seal layer composed of a polyolefin and a second heat seal layer composed of a polyolefin and a heat seal modifier.
[0070] The content of the heat seal modifier in the second heat seal layer is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 40% by mass or less. By making the content of the heat seal modifier in the second heat seal layer 10% by mass or more, the heat sealability of the second heat seal layer can be improved. Also, by making the content of the heat seal modifier in the second heat seal layer 50% by mass or less, the recyclability of the laminate for packaging material of the present invention can be improved.
[0071] When the heat seal layer has the above-mentioned two-layer structure, the thickness of the first heat seal layer is preferably 5 μm or more and 50 μm or less, and more preferably 7 μm or more and 45 μm or less. By making the thickness of the first heat seal layer 5 μm or more, the recyclability of the laminate for packaging material of the present invention and the heat sealability of the first heat seal layer can be improved, and by making the thickness of the first heat seal layer 50 μm or less, the processability of the laminate for packaging material of the present invention can be improved. The thickness of the second heat seal layer is preferably 5 μm or more and 20 μm or less, and more preferably 7 μm or more and 15 μm or less. By making the thickness of the second heat seal layer 5 μm or more, the heat sealability of the second heat seal layer can be improved, and by making the thickness of the second heat seal layer 20 μm or less, the recyclability and processability of the laminate for packaging material of the present invention can be compatible.
[0072] (evaporated film) The laminate for packaging material of the present invention may further comprise a vapor deposition layer at least one between the substrate and the gas barrier laminate and between the gas barrier laminate and the heat seal layer. By providing a vapor deposition film, the gas barrier properties, particularly the oxygen barrier properties and water vapor barrier properties, of the laminate for packaging material of the present invention can be further improved.
[0073] Examples of the vapor-deposited film include vapor-deposited films composed of metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.
[0074] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the laminate for packaging material of the present invention can be further improved, and by making the thickness of the vapor-deposited film 150 nm or less, the occurrence of cracks in the vapor-deposited film can be prevented and the recyclability of the laminate for packaging material of the present invention can be improved.
[0075] For the vapor-deposited film to be an aluminum vapor-deposited film, the OD value is preferably 2 or more and 3.5 or less. This makes it possible to improve the oxygen barrier property and water vapor barrier property while maintaining the productivity of the laminate for packaging material of the present invention. In the present invention, the OD value can be measured in accordance with JIS-K-7361.
[0076] The vapor deposition film can be formed by using a conventional method, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.
[0077] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is 10 -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6 The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The film transport speed can be about 10 to 800 m / min.
[0078] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.
[0079] (adhesive layer) The laminate for packaging materials of the present invention may be provided with an adhesive layer for the purpose of improving adhesion between the surface on which the vapor deposition layer is provided and the surface to be adhered to the vapor deposition layer (adhering surface). That is, when a vapor deposition layer is provided on the surface of the gas barrier laminate, an adhesive layer can be provided between the gas barrier laminate and the vapor deposition layer. When a vapor deposition layer is provided on the surface of the heat seal layer, an adhesive layer can be provided between the vapor deposition layer and the substrate.
[0080] The adhesive layer contains at least one adhesive, and may be a one-component curing type, a two-component curing type, or a non-curing type adhesive. The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but from the viewpoint of environmental load, a solvent-free adhesive is preferably used. Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-component curing urethane adhesives can be preferably used. Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.
[0081] In addition, when the vapor-deposited film of the laminate for packaging materials of the present invention is an aluminum vapor-deposited film, it is preferable to use a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound as a two-component curing adhesive. By configuring the adhesive layer in this way, the oxygen barrier property and water vapor barrier property of the laminate for packaging materials of the present invention can be further improved. When a laminate having a vapor-deposited film is applied to a packaging material, a bending load is applied to the laminate by a molding machine, etc., which may cause cracks in the aluminum vapor-deposited film. By using the specific adhesive as described above, it is possible to suppress a decrease in the oxygen barrier property and water vapor barrier property even if cracks occur in the aluminum vapor-deposited film.
[0082] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule, and the isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.
[0083] As a specific example of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound, the PASLIM series available from DIC Corporation can be used.
[0084] The resin composition may further contain a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.
[0085] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, for example, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.
[0086] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one or more types of orthophthalic acid and its anhydride, and a polyhydric alcohol component containing at least one type selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which the content of orthophthalic acid or its anhydride in the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.
[0087] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Specifically, the polybasic acids include aliphatic polybasic carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecane dicarboxylic acid, unsaturated bond-containing polybasic carboxylic acids such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polybasic carboxylic acids such as 1,3-cyclopentane dicarboxylic acid and 1,4-cyclohexane dicarboxylic acid, aromatic polybasic carboxylic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentane dicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.
[0088] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In the general formula (1), R 1 , R 2 , R 3 are each independently H (hydrogen atom) or a group represented by the following general formula (2). [ka]
[0089] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, R 1 , R 2 , R 3 At least one of the groups represented by formula (2) is represented by the formula (2).
[0090] In the general formula (1), R 1 , R 2 , R 3 At least one of R must be a group represented by general formula (2). 1 , R 2 , R 3 It is preferable that all of them are groups represented by formula (2).
[0091] Also, R 1 , R 2 , R 3 is a group represented by general formula (2), and R 1 , R 2 , R 3 and a compound in which any two of R 1 , R 2 , R 3 may be a mixture of two or more compounds in which all of the above are groups represented by general formula (2).
[0092] X represents an arylene group which may have a substituent and is selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0093] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0094] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0095] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.
[0096] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.
[0097] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R 1 , R 2 , R 3 are each independently "-(CH 2 )n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by general formula (4). [ka]
[0098] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. 1 , R 2 , R 3 At least one of the above is a group represented by general formula (4).
[0099] In the general formula (3), -(CH 2 The alkylene group represented by n1- may be linear or branched. Among these, n1 is preferably 2 or 3, and most preferably 2.
[0100] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.
[0101] When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.
[0102] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0103] In the general formula (3), R 1 , R 2 , R 3 At least one of R is a group represented by general formula (4). 1 , R 2 , R 3 It is preferable that all of them are groups represented by formula (4).
[0104] Also, R 1, R 2 , R 3 is a group represented by general formula (4), and R 1 , R 2 , R 3 and a compound in which any two of R 1 , R 2 , R 3 may be a mixture of two or more compounds in which all of the above are groups represented by general formula (4).
[0105] The polyester polyol having an isocyanuric ring represented by general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or an anhydride thereof in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0106] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.
[0107] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.
[0108] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0109] The polyhydric alcohol component may be an alkylene diol having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, or dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as a triol compound having an isocyanuric ring, orthophthalic anhydride as an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and ethylene glycol as a polyhydric alcohol, are particularly excellent in oxygen barrier properties and adhesion and are therefore preferred.
[0110] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.
[0111] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.
[0112] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.
[0113] The phosphoric acid-modified compound is, for example, a compound represented by the following general formula (5) or (6). [ka] In the general formula (5), R 1 , R 2 , R 3 is a group selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R 4 , R 5represents a group selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group; n represents an integer of 1 to 4, x represents an integer of 0 to 30, and y represents an integer of 0 to 30, except for the case where both x and y are 0.
[0114] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.
[0115] The content of the phosphoric acid-modified compound in the resin composition is preferably from 0.005% by mass to 10% by mass, and more preferably from 0.01% by mass to 1% by mass. By adjusting the content of the phosphoric acid-modified compound to 0.005% by mass or more, the oxygen barrier property and water vapor barrier property of the laminate for packaging material of the present invention can be improved, and by adjusting the content of the phosphoric acid-modified compound to 10% by mass or less, the adhesiveness of the adhesive layer can be improved.
[0116] The resin composition containing the polyester polyol, the isocyanate compound and the phosphoric acid-modified compound may contain a plate-like inorganic compound, which can improve the adhesiveness of the adhesive layer and the bending load resistance of the laminate for packaging material of the present invention. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (such as halloysite, kaolinite, endelite, dickite, nacrite, antigorite, and chrysotile) and pyrophyllite-talc group (such as pyrophyllite, talc, and keroli).
[0117] Examples of the coupling agent include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]
[0118] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).
[0119] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.
[0120] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.
[0121] The resin composition may contain cyclodextrin and / or a derivative thereof, which can improve the adhesiveness of the adhesive layer and the bending load resistance of the laminate for packaging material of the present invention. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and other cyclodextrins in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is substituted with another functional group can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.
[0122] From the viewpoint of compatibility and dispersibility in the resin composition, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound.
[0123] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0124] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0125] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0126] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the thickness of the adhesive layer 0.5 μm or more, the adhesiveness of the adhesive layer can be improved. In addition, when a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound is used, the bending load resistance of the laminate for packaging material can be improved. By setting the thickness of the adhesive layer to 6 μm or less, the processability of the laminate for packaging materials can be improved.
[0127] The adhesive layer can be formed by coating on a substrate or the like and drying using a conventional method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine method, and transfer roll coating.
[0128] (Gas barrier coating film) Within the scope of not impairing the characteristics of the present invention, the laminate for packaging material of the present invention may have, between any layers, a gas barrier coating film containing at least one type of resin composition such as a hydrolysate of a metal alkoxide or a hydrolysis condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. This makes it possible to further improve the oxygen barrier property and water vapor barrier property of the laminate for packaging materials of the present invention. Furthermore, when the vapor-deposited film is made of an inorganic oxide, the occurrence of cracks in the vapor-deposited film can be effectively prevented by providing a gas barrier coating film adjacent to the vapor-deposited film.
[0129] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.
[0130] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.
[0131] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH 3 ) 4 ), tetraethoxysilane (mass%) Si(OC 2 H 5 ) 4 ), tetrapropoxysilane (Si(OC 3 H 7 ) 4 ), tetrabutoxysilane (Si(OC 4 H 9 ) 4 ) etc.
[0132] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organic reactive group-containing organoalkoxysilanes can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. As organoalkoxysilanes having epoxy groups, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned.
[0133] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the alkoxide.
[0134] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.
[0135] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the metal alkoxide. By making the content of the water-soluble polymer in the gas barrier coating film 5 parts by mass or more per 100 parts by mass of the metal alkoxide, the oxygen barrier property and water vapor barrier property of the laminate for packaging material of the present invention can be further improved. Also, by making the content of the water-soluble polymer in the gas barrier coating film 500 parts by mass or less per 100 parts by mass of the metal alkoxide, the film formability of the gas barrier coating film can be improved.
[0136] The thickness of the gas barrier coating film is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate for packaging material of the present invention can be improved. Furthermore, when the gas barrier coating film is provided adjacent to a vapor deposition film composed of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be prevented. Furthermore, by making the thickness of the gas barrier coating film 100 μm or less, the recyclability and processability of the laminate for packaging material of the present invention can be improved.
[0137] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials onto a substrate by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 part by mass, and more preferably 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. By using the sol-gel catalyst in an amount of 0.01 part by mass or more per 100 parts by mass of the metal alkoxide, the catalytic effect can be improved. Furthermore, by setting the amount of the sol-gel catalyst to 1.0 part by mass or less per 100 parts by mass of the metal alkoxide, the thickness of the formed gas barrier coating film can be made uniform.
[0138] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. As the acid, mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as acetic acid, tartaric acid, etc. can be used. The amount of the acid used is preferably 0.001 moles or more and 0.05 moles or less based on the total molar amount of the alkoxide and the alkoxide portion (for example, silicate portion) of the silane coupling agent. By using an acid in an amount of 0.001 mole or more based on the total mole amount of the alkoxide and the alkoxide portion (for example, silicate portion) of the silane coupling agent, the catalytic effect can be improved. Furthermore, by making the amount of the alkoxide and the alkoxide portion (for example, silicate portion) of the silane coupling agent 0.05 mol or less based on the total molar amount, the thickness of the gas barrier coating film formed can be made uniform.
[0139] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total molar amount of the alkoxides. By adjusting the water content to 0.1 mole or more per mole of the total molar amount of the alkoxides, the oxygen barrier property and water vapor barrier property of the laminate for packaging materials of the present invention can be improved. Furthermore, by adjusting the content of water to 100 moles or more per mole of the total molar amount of the alkoxides, the hydrolysis reaction can be carried out quickly.
[0140] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.
[0141] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto a substrate by the above-mentioned conventionally known method, and then dried. This drying causes the polycondensation reaction of the alkoxide and the water-soluble polymer (as well as the silane coupling agent, if the composition contains a silane coupling agent) to proceed further, forming a composite polymer layer. Finally, the composition is heated at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes to form a gas barrier coating film.
[0142] (packaging material) The packaging material of the present invention is characterized in that it is composed of the above-mentioned laminate for packaging materials. The shape of the packaging material is not particularly limited, and may be in the form of a bag as shown in FIG.
[0143] In one embodiment, a bag-shaped packaging material can be produced by folding the laminate of the present invention in half, overlapping the laminate so that the heat seal layer is on the inside, and heat sealing the ends. In another embodiment, the bag-shaped packaging material can also be produced by overlapping two laminates with their heat-sealable layers facing each other, and heat-sealing the ends thereof. In the figure, the shaded areas indicate the heat-sealed areas.
[0144] The heat sealing method is not particularly limited, and can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.
[0145] In one embodiment, the packaging material has a shape of a stand-up pouch having a body and a bottom, as shown in FIG.
[0146] A packaging material in the form of a stand-up pouch can be produced by heat-sealing the above-mentioned laminate into a cylindrical shape with the heat-seal layer on the inside to form a body, and then folding another laminate into a V shape with the heat-seal layer on the inside, sandwiching it from one end of the body, and heat-sealing it to form a bottom.
[0147] The contents filled in the packaging material are not particularly limited, and may be liquid, powder, or gel. In addition, the contents may be food or non-food. After filling the container with the contents, the opening can be heat sealed to form a package. EXAMPLES
[0148] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0149] Example 1 The gas barrier resin layer is made of an ethylene-vinyl alcohol copolymer (EVOH, manufactured by Kuraray Co., Ltd., product name: EVAL E171B, density: 1.14 g / cm 3 , melting point: 165°C, MFR: 1.7g / 10min, ethylene content: 44% by mass, The adhesive resin layer is made of polyolefin (manufactured by Mitsui Chemicals, Inc., product name: Admer QF551, density: 0.89 g / cm 3 , melting point: 135°C, MFR: 2.5g / 10min), and polypropylene (manufactured by TPC Corporation, product name: FL7540L, density: 0.90g / cm3) constituting the polyolefin resin layer. 3 , melting point: 138℃, MFR: 7.0g / 10min) The mixture was co-extruded using the T-die method and stretched 3.1 times in both the longitudinal direction (MD) and the transverse direction (TD) to produce a gas barrier laminate having a structure of a gas barrier resin layer (1 μm) / adhesive resin layer (2 μm) / polyolefin resin layer (15 μm).
[0150] On the gas barrier resin layer of the gas barrier laminate prepared as described above, an aluminum vapor deposition film having a thickness of 30 nm was formed by a PVD method. The vapor deposition concentration (OD value) of the vapor deposition film thus formed was measured and found to be 3.0.
[0151] As a substrate, a biaxially oriented polypropylene film having a thickness of 18 μm (manufactured by Toyobo Co., Ltd., product name: P2108) was prepared. An image was formed on one surface of the biaxially stretched polypropylene film by gravure printing using a solvent-based gravure ink (Finart, manufactured by DIC Graphics Co., Ltd.).
[0152] The aluminum vapor deposition film-formed surface of the gas barrier laminate was laminated to the image-formed surface of a biaxially stretched polypropylene film via a two-component curing polyurethane adhesive (manufactured by Rock Paint Co., Ltd., trade name: RU-3600 / H-689).
[0153] Next, the polypropylene was extruded by a T-die method to obtain an unstretched polypropylene film having a thickness of 35 μm that constitutes the heat seal layer.
[0154] On one side of the unstretched polypropylene film prepared as described above, an aluminum vapor deposition film having a thickness of 30 nm was formed by the PVD method. The vapor deposition concentration (OD value) of the vapor deposition film thus formed was measured and found to be 3.0.
[0155] The polyolefin resin layer of the gas barrier laminate and the aluminum vapor deposition film-formed surface of the unstretched polypropylene film were laminated via a two-component curing polyurethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-3600 / H-689) to obtain a laminate for packaging material of the present invention. The proportion of the same polyolefin (PP) in the laminate thus obtained was 92% by mass.
[0156] Example 2 Except for changing the thickness of the aluminum vapor-deposited film provided on the gas barrier laminate and the heat seal layer to 20 nm and changing the OD value of the vapor-deposited film to 2.0, the laminate for packaging material of the present invention was produced in the same manner as in Example 1. The proportion of the same polyolefin (PP) in the laminate thus obtained was 92% by mass.
[0157] Example 3 The laminate for packaging material of the present invention was produced in the same manner as in Example 1, except that the two-component curing polyurethane adhesive used for bonding the aluminum vapor deposition film-formed surface of the gas barrier laminate to the image-formed surface of the biaxially stretched polypropylene film, and for bonding the polyolefin resin layer of the gas barrier laminate to the aluminum vapor deposition film-formed surface of the unstretched polypropylene film, was changed to a two-component curing adhesive containing polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound (manufactured by DIC Corporation, product name: PASLIM VM001 / VM102CP). The proportion of the same polyolefin (PP) in the laminate thus obtained was 92% by mass.
[0158] Comparative Example 1 A laminate for packaging materials was obtained in the same manner as in Example 1, except that an unstretched polypropylene film having a thickness of 18 μm (manufactured by Toyobo Co., Ltd., product name: P1108) was used as the substrate. The proportion of the same polyolefin (PP) in the laminate thus obtained was 92 mass%.
[0159] Comparative Example 2 The above polypropylene was extruded by a T-die method to produce an unstretched polypropylene film having a thickness of 180 μm. This was then stretched 3.1 times in each of the machine direction (MD) and the transverse direction (TD) to obtain a stretched polypropylene film a having a thickness of 18 μm.
[0160] An image was formed on one surface of the stretched polypropylene film prepared as described above by gravure printing using a solvent-based gravure ink (Finart, manufactured by DIC Graphics Corporation).
[0161] The above polypropylene was extruded by a T-die method to produce an unstretched polypropylene film having a thickness of 180 μm. This was then stretched 3.1 times in each of the machine direction (MD) and the transverse direction (TD) to obtain a stretched polypropylene film b having a thickness of 18 μm.
[0162] The image-forming surface of the stretched polypropylene film a and the stretched polypropylene film b were laminated together via a two-component curing polyurethane adhesive (manufactured by Rock Paint Co., Ltd., trade name: RU-3600 / H-689).
[0163] Next, the polypropylene was extruded by a T-die method to obtain an unstretched polypropylene film having a thickness of 35 μm.
[0164] On one side of the unstretched polypropylene film prepared as described above, an aluminum vapor deposition film having a thickness of 30 nm was formed by the PVD method. The vapor deposition concentration (OD value) of the vapor deposition film thus formed was measured and found to be 3.0.
[0165] The stretched polypropylene film b, the vapor-deposited film-formed surface of the unstretched polypropylene film, and the image-formed surface of the biaxially stretched polypropylene film were laminated via a two-liquid curing polyurethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-3600 / H-689) to obtain a laminate for packaging materials. The proportion of the same polyolefin (PP) in the laminate thus obtained was 92% by mass.
[0166] Comparative Example 3 A laminate for packaging materials was obtained in the same manner as in Example 1, except that a 12 μm-thick stretched polyester film (manufactured by Toyobo Co., Ltd., product name: E5100) was used as the substrate. The proportion of the same polyolefin (PP) in the thus obtained laminate was 74 mass%.
[0167] <<Recyclability evaluation>> The recyclability of the laminates for packaging materials obtained in the above Examples and Comparative Examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The content of the same polyolefin in the laminate for packaging material was 80% by mass or more. ×: The content of the same polyolefin in the laminate for packaging material was less than 80 mass %.
[0168] <<Strength evaluation>> The laminates for packaging materials produced in the above Examples and Comparative Examples were measured for strength when pierced with a needle having a diameter of 0.5 mm using a tensile tester (manufactured by Orientec Co., Ltd., product name: RTC-1310A). The piercing speed was 50 mm / min. The measurement results are summarized in Table 1.
[0169] <<Heat resistance evaluation>> Two test pieces each measuring 80 mm long x 80 mm wide were prepared from the laminates for packaging materials obtained in the above Examples and Comparative Examples. Two test pieces were overlapped with the heat seal layers facing each other, and three sides were heat sealed at 150°C to prepare a small pouch-shaped packaging material. The prepared packaging material was visually observed, and the heat resistance of the laminate for packaging material was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: No wrinkles or the like were observed on the surface of the packaging material, and no adhesion to the heat seal bar was observed. ×: Wrinkles or the like were generated on the surface of the packaging material, and adhesion to the heat seal bar was observed, and bags could not be made.
[0170] <<Printability evaluation>> In the above examples and comparative examples, the images formed on the substrate were visually observed, and the printability thereof was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The dimensional stability during printing was good, and good images without rubbing, bleeding, etc. could be formed. ×: The film expanded or contracted during printing, causing rubbing or bleeding in the formed image.
[0171] <<Oxygen Barrier Evaluation>> The laminates for packaging materials obtained in the above Examples and Comparative Examples were cut into A4 size pieces, and the oxygen permeability (cc / m) was measured using OXTRAN 2 / 20 manufactured by MOCON, USA, at 23°C and a relative humidity of 90%. 2 / day / atm) were measured. The measurement results are summarized in Table 1.
[0172] <<Water vapor barrier property evaluation>> The laminates obtained in the above Examples and Comparative Examples were cut to A4 size, and the water vapor permeability (g / m) was measured under an environment of 40°C and a relative humidity of 90% using a PERMATRAN 3 / 31 manufactured by MOCON, USA. 2 / day / atm) were measured. The measurement results are summarized in Table 1.
[0173] <Bending load resistance evaluation> The laminate for packaging material obtained above was subjected to a bending load (stroke: 155 mm, bending motion: 440°) five times in accordance with ASTM F 392 using a Gelbo Flex Tester (Tester Sangyo Co., Ltd., product name: BE1006BE). After the bending load, the oxygen permeability and water vapor permeability of the laminate were measured. The measurement results are summarized in Table 1.
[0174] <<Heat sealability test>> The laminates for packaging materials obtained in the above Examples and Comparative Examples were cut to 10 cm x 10 cm to prepare sample pieces. The sample pieces were folded in half so that the heat seal layer was on the inside, and then heated at 150°C and under a pressure of 1 kgf / cm. 2 An area of 1 cm x 10 cm was heat sealed under the conditions of 100° C., 1 sec. The heat-sealed sample pieces were cut into strips with a width of 15 mm, and both ends that were not heat-sealed were held in a tensile tester to measure the peel strength (N / 15 mm) at a speed of 300 mm / min and a load range of 50 N. The measurement results are summarized in Table 1. The laminate for packaging material obtained in Comparative Example 1 was adhered to the heat seal bar, and peel strength could not be measured, so it was marked as "-".
[0175] [Table 1] [Explanation of symbols]
[0176] 10: Laminate for packaging material, 11: Substrate, 12: Gas barrier laminate, 13: Heat seal layer, 14: Gas barrier resin layer, 15: Polyolefin resin layer, 16: Vapor deposition film, 17: Adhesive layer, 18: Adhesive resin, 19: First heat seal layer, 20: Second heat seal layer
Claims
1. The present invention includes at least a substrate, a gas barrier laminate, and a heat seal layer, the substrate and the gas barrier laminate are stretched resin films, The gas barrier laminate is a co-extrusion stretched resin film of a gas barrier resin layer and a polyolefin resin layer, the substrate, the polyolefin resin layer and the heat seal layer are made of polyethylene or polypropylene; 13. A laminate for packaging materials, comprising: a gas barrier resin layer having a thickness smaller than a thickness of the polyolefin resin layer.
2. 2. The laminate for packaging materials according to claim 1, wherein the content of the polyolefin in the entire laminate for packaging materials is 80 mass % or more.
3. 3. The laminate for packaging materials according to claim 1, further comprising a deposition layer at least one between the substrate and the gas barrier laminate and between the gas barrier laminate and the heat seal layer.
4. The laminate for packaging materials according to claim 3 , further comprising an adhesive layer between the substrate and the vapor-deposited film and between the gas barrier laminate and the vapor-deposited film.
5. the vapor-deposited film is an aluminum vapor-deposited film, The laminate for packaging materials according to claim 4 , wherein the adhesive layer comprises a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound.
6. The laminate for packaging materials according to any one of claims 1 to 5, wherein the gas barrier laminate comprises an adhesive resin layer between the gas barrier resin layer and the polyolefin resin layer.
7. A packaging material comprising the laminate for packaging materials according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for producing gas barrier film
JP2002309023A
Polyolefin composite film
JP2004216565A
Easily opening co-extruded film, lid material and deep-drawn vessel using film
JP2006281675A
Laminated material for toothpaste tube and tubular toothpaste container
JP2012144290A
Multilayer barrier film, packaging laminate containing the film, packaging container formed from the packaging laminate, and method for manufacturing the film.
JP2014531341A